Assessment of Quality of Life of a Patient with Acute Type A Aortic Dissection Who Underwent Cardiac Rehabilitation After Surgical Treatment Under Artificial Circulation - V. V. Vladimirov; A. A. Bruikov; V. S. Selyaev; L. S. Kokov; A. V. Redkoborody; I. V. Ivanov; R. Sh. Muslimov; S. V. Zhuravel (Неотложная медицинская помощь)
The article presents a clinical case of treating a 42-year-old patient with acute aortic dissection (type I according to DeBakey classification), who underwent an individual cardiac rehabilitation program in the early postoperative period after surgical treatment in the volume of reconstruction of the thoracic aorta using hybrid technology under conditions of artificial circulation and circulatory arrest. Early rehabilitation after aggressive surgical intervention ensured the most complete restoration of health, psychological status and working capacity of the patient in a minimum period of time.